2021
DOI: 10.1002/rmb2.12412
|View full text |Cite
|
Sign up to set email alerts
|

Novel approaches to the management of recurrent pregnancy loss: The OPTIMUM (OPtimization of Thyroid function, Thrombophilia, Immunity, and Uterine Milieu) treatment strategy

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 73 publications
0
25
0
Order By: Relevance
“…Cytokines such as tumor necrosis factor‐α, interleukin‐6 and interferon‐γ are synthesized in large quantities by Th1 cells in RSA patients, causing an excessive inflammatory response in the body 34 . In addition, Kuroda et al 36 . showed that the Th1/Th2 ratio was obviously lower in RSA patients after vitamin D treatment, which validated the relationship between serum vitamin D concentrations and the Th1/Th2 ratio.…”
Section: Discussionmentioning
confidence: 87%
“…Cytokines such as tumor necrosis factor‐α, interleukin‐6 and interferon‐γ are synthesized in large quantities by Th1 cells in RSA patients, causing an excessive inflammatory response in the body 34 . In addition, Kuroda et al 36 . showed that the Th1/Th2 ratio was obviously lower in RSA patients after vitamin D treatment, which validated the relationship between serum vitamin D concentrations and the Th1/Th2 ratio.…”
Section: Discussionmentioning
confidence: 87%
“…There was also no difference in the chromosomal aberration rate between the factors for recurrent pregnancy loss, with or without thrombophilia, and antithrombotic therapy; only advancing maternal age was significantly correlated with increased embryo chromosomal aberration rates. 19 On the contrary, according to Kurodawa, 20 the live birth rate in thrombophilia patients treated with low‐dose aspirin increased in all patients, except for those older than 40 years old. Our patients were treated with low‐molecular‐weight heparin, not aspirin, but there was no difference regarding age.…”
Section: Discussionmentioning
confidence: 98%
“…The diagnosis of CE was defined as five or more CD138‐positive cells in 10 random areas at ×10 magnification based on our previous studies. 26 , 27 …”
Section: Methodsmentioning
confidence: 99%
“…None of the patients had chronic endometritis (CE) resulting from CD138 immunostaining of the endometrium or abnormal complete blood count data. The diagnosis of CE was defined as five or more CD138‐positive cells in 10 random areas at ×10 magnification based on our previous studies 26,27 …”
Section: Methodsmentioning
confidence: 99%